Samakālīna Bhāratīẏa rājanīti ebaṃ Rabīndrasāhitya - Rāẏa, Jībendu (Sāhityaśrī, 1980)
Study of the impact of Indian political movements of the period on the writings of Rabindranatha Tagore, 1861-1941.